The Utilization of Plastics Waste in Flexible Pavement Hot Rolled Sheet and Asphalt Concrete Wearing Course with Marshall Immersion and Cantabro Test. (April 2020) - Adhitya, B B; Pataras, M; Kadarsa, E; Nurainiyah, F
Abstract: Road was a transportation infrastructure that connect a place to the other place. Road pavement should be utilize resources efficiently, effectively and eco friendly. One important material that used for road pavement is asphalt. Plastics are very useful in daily life but the existence of plastic these day became problems to the environment especially the plastic waste. Plastic waste has negative impact for out environment because it was hard to decompose. This research was done to know the utilization of hot rolled sheet wearing course (HRS-WC) and asphalt concrete wearing course (AC-WC) mixture by using waste of plastic such as cups, plastic bags, and plastic snacks with Marshall immersion test and cantabro test. The result that can be concluded are optimum aspal content with each kind of plastics. Then Marshall Immersion test with the index of retained strength (IRS) value and cantabro test value.